First report of gastroschisis in black-eared opossum (Didelphis aurita) - Roger da Silva Carlos; Larissa Solino de Abreu Franco; Maria Clara Paschoalini Liquer; Anita Ladeira Gesualdi; Eduardo Carlos de Souza Muniz; Beatriz Salles Monteiro; Álvaro José Bittencourt Bastos; Leonardo Serafim da Silveira (Brazilian Journal of Veterinary Pathology, 2025)
Black-eared opossums (Didelphis aurita) are neotropical marsupials least concern with extinction in Brazil. Pathologies involving this species are rarely described, and gastroschisis has never been reported before. This study aims to report a case of gastroschisis in a black-eared opossum newborn and describe the main characteristics observed. A newborn black-eared opossum in the developmental stage in marsupial pouch was received lifeless by Núcleo de Estudos e Pesquisas em Animais Selvagens (NEPAS) of Universidade Estadual do Norte Fluminense Darcy Ribeiro (UENF). The animal was examined externally, and herniated intestinal loops were observed without the presence of the peritoneum covering them, indicating gastroschisis. This report aims to contribute to the literature on small marsupial medicine by describing the occurrence of this malformation in an individual of D. aurita.